Pengaruh Perubahan Suhu pada Properti Adsorpsi dan Desorpsi Thermosensitive NIPAM-co¬-DMAAPS Gel - Jovanio Bosco Chu Gomes Amaral; Desi Ratnasari; Prida Novarita Trisanti; Sumarno Sumarno; Eva Oktavia Ningrum (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Adsorbent gels with ability to absorb and desorb ion simultaneously with temperature swing are synthesized by free radical copolymerization reaction of N-isopropylacrylamide (NIPAM) and N,N-dimethyl(acrylamidopropyl)ammonium propane sulfonate (DMAAPS). In this study, NIPAM acts as a thermosensitive agent and DMAAPS as an adsorbent agent. The purposes of this research are to investigate the effects of temperature on the swelling, adsorption and desorption behaviors of ion onto thermosensitive NIPAM-co-DMAAPS gel, and to study the relationship between these behaviors. NaNO3 solution was selected as the target solution and used in swelling, adsorption and desorption test. Swelling test was done by measuring diameter of the cylindrical gel after and before immersion in the NaNO3 solution for 12 hours. The result revealed that at high temperature, the amount of ion adsorbed onto the gels was low. On the contrary, the gel exhibited a high degree of swelling and high amount of ion desorbed from the gel. Moreover, higher concentration of NaNO3 solution resulting in the higher value of the swelling degree, adsorption and desorption ability. Based on the relationship between the swelling properties and adsorption properties, it can be concluded that at a lower degree of swelling, the amount of ion adsorbed onto the gels showed a constant value. However, the amount of ion adsorbed decrease with further increasing the swelling degree.